Wybrane innowacje wdrożone przez przedsiębiorstwa handlu detalicznego, ich źródła a wybory konsumentów miasta Tarnowa w latach 2014–2016 - Kolak, Zbigniew (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
This article is led to describe, is based on the chosen and the particular innovations which were used by the corporations (firms, companies) of the retail trade in Tarnow from 2014 to 2016 and also presents some sources of those innovations in the area. The way to obtain the customers and to have a good relations with them, also to increase the quality of the products, ought to be the main point in these preparations or researches to achieve the success. The other zones, where the innovations are conducted, must be preparing the best offers, decreasing all the costs, which are connected with the service. What is more, and should be mentioned, is the improvement of the work’s condition. This is very essential matter. All the factors, were used in the analyses were prepared to present how the customers can experience and if they need all these changes and innovations. Moreover, the important question in this article is, if the innovations can help some companies to have better development in their business. What is also very essential, if the clients notice the changes and what is done, by the proper companies, to help the customers to make the right decisions.
Keywords: innovation; the company of the retail trade; the customer- the main target of these actions; economy